2019
DOI: 10.1152/japplphysiol.00729.2018
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of sex differences in the acute impact of oscillatory shear stress on endothelial function

Abstract: Acutely imposed oscillatory shear stress (OSS) reduces reactive hyperemia flow-mediated dilation (RH-FMD) in conduit arteries of men; however, whether a similar impairment occurs in women or with FMD in response to a controlled, sustained shear stress stimulus (SS-FMD) is unknown. The purpose of this study was to determine the impact of OSS on RH-FMD and SS-FMD in men and women. OSS was provoked in the brachial artery using a 30-min forearm cuff inflation (70 mmHg). Healthy men [ n = 16, 25 yr (SD 3)] and wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
3
10
1
Order By: Relevance
“…This is in contrast with previous reports suggesting that female conduit arteries may be protected against proatherogenic perturbations in shear stress (52). For instance, Tremblay et al (50) observed a reduction in FMD stimulated by a sustained increase in shear stress in men, but not women, after a similar 30-min forearm cuff intervention. Likewise, Vranish et al (52) observed preserved popliteal artery reactive hyperemia-induced FMD in women after 3 h of uninterrupted sitting (isolated low mean shear stress) compared with a consistent, considerable reduction in men.…”
Section: Are Women Susceptible To Oscillatory and Low Mean Shear Stress-induced Reductions In Fmd?contrasting
confidence: 84%
See 1 more Smart Citation
“…This is in contrast with previous reports suggesting that female conduit arteries may be protected against proatherogenic perturbations in shear stress (52). For instance, Tremblay et al (50) observed a reduction in FMD stimulated by a sustained increase in shear stress in men, but not women, after a similar 30-min forearm cuff intervention. Likewise, Vranish et al (52) observed preserved popliteal artery reactive hyperemia-induced FMD in women after 3 h of uninterrupted sitting (isolated low mean shear stress) compared with a consistent, considerable reduction in men.…”
Section: Are Women Susceptible To Oscillatory and Low Mean Shear Stress-induced Reductions In Fmd?contrasting
confidence: 84%
“…Furthermore, this reduction was evident in both men and women. A previous study from our laboratory identified a decrease in reactive hyperemia-stimulated FMD in women following the forearm cuff intervention; however, there was a concomitant reduction in SR AUC such that covariate-correcting for the shear stress stimulus abolished the reduction in FMD (50). Through implementation of a longer duration of supine rest before preintervention measures (45 min versus 30 min), we were able to mitigate changes in the shear stress stimulus from before to after intervention.…”
Section: Impact Of Cuff Intervention On Fmdmentioning
confidence: 74%
“…Although often unreported (Schreuder et al., , b), shear AUC, the stimulus for the FMD response, is commonly revealed to be unchanged (Thijssen et al., , ) afer 30 min of SDCI. However, two recent studies by Tremblay and colleagues corroborate the findings of the present study by identifying a significant reduction in shear AUC after a 30 min SDCI intervention (Tremblay, Howe, Ainslie, & Pyke, , ), implicating a change in the stimulus (shear AUC), not the response (BA FMD) after the SDCI intervention.…”
Section: Discussionsupporting
confidence: 88%
“…Another interesting finding in the present study was that, independent of group, the conduit arteries did not display any alterations in vascular function associated with acute increases in retrograde flow. This has been reported previously in only one study using the SDCI technique (Tremblay, Stimpson, & Pyke, ), but similar findings have been revealed in the lower limb conduit arteries after 1 h of reduced anterograde flow (Vranish et al., ) and in bed‐rest studies that reported similar or improved BA FMD measurements after 5–7 days of physical inactivity (Bonnin et al., ; Hamburg et al., ). Taken together, this might highlight a potential resiliency of conduit artery function in response to this specific type (increased retrograde/oscillatory shear) and magnitude (60 mmHg) of altered shear patterns.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation